2009
DOI: 10.4067/s0717-95022009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic Vein: Detail of its Anatomy in the Deltopectoral Triangle

Abstract: The cephalic vein shows a scarce description, especially in the deltopectoral triangle, and its ending in the axillary vein. Some established considerations such as "superficial vein, located in the deltopectoral groove, accompanied by braches of the thoraco-acromial artery, which ends in the deltopectoral triangle in the shape of fan arch" should be reevaluated. Procedures difficulties in the la catheterization deserve for a more accurate description. A descriptive, prospective study is performed. The goal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Numerous variations in the course and terminal drainage of the cephalic vein have been described including persistence of the jugulocephalic vein [18], absence of cephalic vein [19][20][21][22][23], cephalic vein draining into the external or internal jugular vein, cephalic vein draining into the subclavian vein or into the junction of subclavian and internal jugular vein, cephalic vein draining into the basilic vein [24] and accessory cephalic vein [25]. Concerning frequency of the absence of the cephalic vein, Loukas et al [19] report 5% Le Saout et al [20] During embryonic life principle arm vein remains in caudal or ulnar positions and joins the lateral thoracic (thoracoepigastric) vein to form the primitive subclavian trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous variations in the course and terminal drainage of the cephalic vein have been described including persistence of the jugulocephalic vein [18], absence of cephalic vein [19][20][21][22][23], cephalic vein draining into the external or internal jugular vein, cephalic vein draining into the subclavian vein or into the junction of subclavian and internal jugular vein, cephalic vein draining into the basilic vein [24] and accessory cephalic vein [25]. Concerning frequency of the absence of the cephalic vein, Loukas et al [19] report 5% Le Saout et al [20] During embryonic life principle arm vein remains in caudal or ulnar positions and joins the lateral thoracic (thoracoepigastric) vein to form the primitive subclavian trunk.…”
Section: Discussionmentioning
confidence: 99%
“…3 This is in contrast to another anatomical study where the authors believe that the CV always takes a "deep" course in the deltopectoral triangle. 4 With a rate of CV absence ranging from 5 to 19.7% 3e5 reported in the literature, as well as inconsistent depth within the deltopectoral triangle, the reconstructive breast surgeon ought to proceed with caution; As the CV is not always the consistent saviour it is widely thought to be the surgeon must have secondary strategies prepared when using it as a salvage conduit.…”
mentioning
confidence: 99%
“…Many authors have reported the anatomical variants of the CV: absent or very thin CV [3,10,14,20] or accessory CV [3,4]. Absence of the CV was found in 3% of male and 1% of female subjects [3]; in these cases, the deltopectoral part of the CV may also be small or absent, and thus, the median antebrachial vein is usually enlarged to drain the area of the CV.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of the CV was found in 3% of male and 1% of female subjects [3]; in these cases, the deltopectoral part of the CV may also be small or absent, and thus, the median antebrachial vein is usually enlarged to drain the area of the CV. The CV also displays high variability concerning its termination into the basilic vein [3], the internal jugular vein [15], the subclavian vein [10] or the external jugular vein [1,6,7,9,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation